Pengaruh Perbandingan Rumput Laut (Gracilaria Sp.) Dengan Bawang Putih (Alium sativum L.) Terhadap Karakteristik Kaldu Rumput Laut - Lina Herlinawati; Ida Ningrumsari; Rini Sitawati; Eca Amelia (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2022)
This research on making seaweed seasoning powder is expected to provide an alternative safe flavoring material because it comes from natural food and is one of the diversified products of processed local seaweed that is widely cultivated in Indonesia. This study also aims to determine the effect of the ratio of dried seaweed and garlic powder on water content, ash, dissolved solids, and organoleptic properties of seaweed seasoning powder. The experimental design that will be used in this study is a Completely Randomized Design (CRD) pattern with one variable, namely the ratio of dried seaweed and garlic at levels 1:2, 1:1, and 2:1. The results showed that the ratio of dried seaweed and garlic powder had a significant effect on water content, ash content, total soluble solid (TSS), taste, aroma, and texture seaweed seasoning powder. The ratio of dried seaweed and garlic powder had no significant effect on the color of seaweed seasoning powder. The best treatment was  a ratio of seaweed and garlic powder of 1:2 having an average value of color 4.13, taste 3.29, aroma 3.62, texture 4.03, water content 7.12%, ash content 2.91, and total dissolved solids of 89.14%.